KAJIAN BEBAN PENDORONG MESIN PEMOTONG TEMPE - Catur Pramono; Endang Mawarsih; Hendy Kurniawan (Journal of Mechanical Engineering, 2018)
One of the most important sources of vegetable protein to improve people's nutrition is soybean. Soybean is a type of food that is safe for consumption, good for maintaining health, and the price is cheap. Soybean is a type of legume plant that is often used as the basic ingredient of tempe. Tempe making through fermentation by Rhizopus sp. Processed foods tempe until now is still a culinary in Indonesia to overseas. The purpose of this study is to assess the engine driving load for tempe cutters 2kg, 3kg and 4kg for tempe chips production. The results showed that the tempe 3kg tempe load was most suitable for tempe production.